MINERALOGICAL STUDY OF INORGANIC INTERCALATED SEAMS AT ACHLADA LIGNITE DEPOSITS (NW GREECE) - Oikonomopoulos, I.; Perraki, Th.; Kaouras, G.; Antoniadis, P. (Bulletin of the Geological Society of Greece, 2007)
We study the inorganic intercalated horizons of "Achlada" lignite deposits in Fiorina basin combining the mineralogical study and initial palaleobotanical data. The samples were investigated by means of X-ray diffraction (XRD), thermogravimetric (TG/DTG) and differential thermal analysis (DTA) and Fourier Transform (FT-IR) spectroscopy. The clay minerals prevail in all samples, with illite being the dominant phase, kaolinite and chlorite to be the next. No smectite was found. In addition to clay minerals, the other mineral phases identified are mainly quartz and feldspars. The presence of siderite, in the majority of the samples, is also remarkable. The illite, kaolinite and chlorite percentages of the thicker inorganic horizon were correlated to the paleoenvironmental data. The classification of this particular material into appropriate ternary diagrams shows that the studied clays may be used in the production of red-stoneware products in ceramic industry. This analysis of clay minerals was made to evaluate the industrial use of clay horizons they belong to and understand their multi-dimensional role in coal-bearing process